Medication use during pregnancy in Arab countries: A narrative review - Sura Habeeb Hattab Al-Ani; Ahmad Habeeb Dala Ali; Noordin Othman (Romanian Medical Journal, 2023)
Pregnancy is an important event in women’s life as it involves various physiological and anatomical alterations to match and accommodate with the development of the fetus. Due to c-morbidities and pregnancy related complications, pregnant women often requires medical management which includes medication use. We reviewed the literature for studies that assessed medication use among pregnant women in the Arabian countries. Prevalence of medication use among pregnant women from Arabian countries varied from 40% to 98.2%. The most commonly used medications were vitamin and supplements, analgesics, antibiotics, and herbal medicines. The most frequently reported justification for self-medication were: inconvenience, less expensive, previous experience with disease, and that the diseases are not serious. In conclusion, the use of medications during pregnancy were found to be prevalent among pregnant women in the Arabian countries.